2018
DOI: 10.3390/molecules23112966
|View full text |Cite
|
Sign up to set email alerts
|

The H2S Donor GYY4137 Stimulates Reactive Oxygen Species Generation in BV2 Cells While Suppressing the Secretion of TNF and Nitric Oxide

Abstract: GYY4137 is a hydrogen sulfide (H2S) donor that has been shown to act in an anti-inflammatory manner in vitro and in vivo. Microglial cells are among the major players in immunoinflammatory, degenerative, and neoplastic disorders of the central nervous system, including multiple sclerosis, Parkinson’s disease, Alzheimer’s disease, and glioblastoma multiforme. So far, the effects of GYY4137 on microglial cells have not been thoroughly investigated. In this study, BV2 microglial cells were stimulated with interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Specifically, the protective effects of H 2 S in neurons and astrocytes that have been reported [59,60] suggest that this molecule could be beneficial in MS. Along the same line, we and others have previously shown that H 2 S potently affects the inflammatory activity of microglia [39,47]. However, the effect of H 2 S on encephalytogenic cells during MS and EAE has not been addressed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Specifically, the protective effects of H 2 S in neurons and astrocytes that have been reported [59,60] suggest that this molecule could be beneficial in MS. Along the same line, we and others have previously shown that H 2 S potently affects the inflammatory activity of microglia [39,47]. However, the effect of H 2 S on encephalytogenic cells during MS and EAE has not been addressed.…”
Section: Discussionmentioning
confidence: 88%
“…Murine BMDCs were differentiated in vitro in the presence of GM-CSF and matured under the influence of LPS. GYY4137 (200 M) was applied simultaneously with LPS for 24 h. The dose of 200 M was chosen as it was previously shown to be efficient in modulating the phenotypic and functional properties of microglial cells [ 47 ] without affecting cell viability. Indeed, at this dose, GYY4137 did not affect the DC viability ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also studied the possible diagnostic and prognostic value of TSPAN32 expression in PBMC of MS patients, on the course of the disease. The use of whole-genome expression databases has been largely exploited [25][26][27][28] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, including immunoinflammatory and autoimmune diseases [29][30][31][32][33][34][35][36], cancer [37][38][39], and has allowed dismantling pathogenetic pathways [40][41][42], along with the identification of novel tailored therapeutic targets [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we first analyzed the expression levels of IL37, SIGIRR, and IL18R1 in circulating immune cells from MS patients. In particular, we performed a DNA microarray analysis that represents a useful in silico tool for the better understanding of pathogenic pathways and the possible prediction of novel diagnostic therapeutic strategies, as it has been shown in a variety of clinical settings, such as autoimmune and immunoinflammatory diseases [38][39][40][41][42][43][44] and cancer [45][46][47][48][49][50][51], leading to the identification of novel therapeutic targets [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%